The Value of Surveys in Pediatric Surgery - Zani, Augusto; Zani-Ruttenstock, Elke; Eaton, Simon; Pierro, Agostino (European Journal of Pediatric Surgery, 2015)
Surveys are an important research tool to evaluate the practice patterns of physicians. In the medical literature, practice surveys are increasingly used in specialties, such as pediatric surgery, characterized by the lack of sufficient evidence-based literature due to the rarity of the conditions treated. To maintain a level that yields to a meaningful scientific contribution the design, data collection and analysis of the survey have to be rigorous. Herein, we describe the general principles of survey methodology, we report the benefits and limitations of this statistical method, and we discuss the value of surveys in pediatric surgery.
Keywords: survey; questionnaire; methodology; evidence based